RJC 2021
DOI: 10.31788/rjc.2021.1446353
|View full text |Cite
|
Sign up to set email alerts
|

GENUS Pothos: A REVIEW OF CHEMICAL CONSTITUENTS AND BIOLOGICAL ACTIVITIES

Abstract: Pothos is a genus of flowering plants that belongs to the family Araceae. It plays a vital role in developing countries as folk medicine. Numerous compounds have been reported from Pothos, out of which some compounds have shown prominent bioactivities. The biological studies of this genus reported various activities including antimicrobial, anticancer, antioxidant, antipyretic, anti-diabetes, bronchodilator, burn wound healing, anticariogenic, thrombolytic etc. This review summarizes research carried out on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous study was identified the secondary metabolites in P.tener were flavonoid, phenol and glycosides. (Dutta et al, 2021;Nugraha et al, 2019).…”
Section: Figure 2 Pothos Tenner From Bantimurung Waterfallsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous study was identified the secondary metabolites in P.tener were flavonoid, phenol and glycosides. (Dutta et al, 2021;Nugraha et al, 2019).…”
Section: Figure 2 Pothos Tenner From Bantimurung Waterfallsmentioning
confidence: 99%
“…The varies result of plant metabolites among the crude drugs and the extracts needs confirmation by another separation technique, such as TLC with specific reagents (see Table 3). (Cai, 2014;Dutta et al, 2021;Liu et al, 2019) The TLC result of EE and ME have identified the presence of phenol and flavonoid in P.tener.…”
Section: Thin Layer Chromatographymentioning
confidence: 99%
See 3 more Smart Citations